IDEOLOGICAL DECONSTRUCTION OF THE PROMOTIONAL MEDIA IN BALI CULTURAL TOURISM - Udayana, AA Gde Bagus; Atmadja, Nengah Bawa; Dhana, I Nyoman (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2017)
The regional regulation issued by the Provincial Government Number 2 of 2012 defines that Tri Hita Karana is a Hindu philosophy explaining the three things which contribute to prosperity. Therefore, the promotional media of tourism should be ideally based on the ideology of Tri Hita Karana. However, the fact shows that it has been marginalized in the promotional media of the Bali cultural tourism. In relation to this, three main theories are used in the present study. They are the theory of deconstruction, the theory of practice, and the theory of social reality construction. The qualitative, descriptive, and interpretative methods were employed to analyze the data, which were collected through in-depth interview, observation and documentary study. Based on the result of the study, it can be concluded that the capitalistic ideology, the ideology of cultural dualism, the ideology of consumerism, the ideology of commercialism, the ideology of totalitarianism, and the ideology of pseudo-social responsibility have been responsible for the marginalization of the ideology of Tri Hita Karana in the promotional media of the Bali cultural tourism. The system used to deconstruct the promotional media of the Bali cultural tourism involves the government, private companies, and the graphic design consultants. They are oriented towards their respective ideology and interest. The ideology and interest-oriented promotional media of the Bali cultural tourism affect the image of Bali as a tourist destination. The implications are as follows: Bali is an area of the culture of tourism; it is an area where postmodern people live; it is an area where glocalization takes place; it is an area where modern spirituality develops; it is also an area where the identity of the Balinese people and culture is shown not to be in accordance with the fact.